Deskripsi Keterampilan Kolaborasi Mahasiswa Pendidikan Kimia FKIP UNTAN Pada Praktikum Kimia Dasar - Dyan Hayuningtrisna Hadiwangsa; Hairida; Rahmat Rasmawan; Eny Enawaty; Tulus Junanto (Jurnal Penelitian Pendidikan IPA, 2024)
Collaboration Skills (CS) are important to master in 21st century and must be developed for academic and career success in the real world. The study aims to describe the collaboration skills of Chemistry Department students at FKIP UNTAN through practicum learning activities in the laboratory. The research method is a quantitative descriptive research. The Research participants were 63 students who took basic chemistry practicum courses. Data collection was carried out using observation techniques with the help of two observers and collaboration skills observation sheets, that had been validated by two experts in the field of evaluation. The results showed that, the average of percentage value obtained for each indicator such as: contributing to group discussions (96.83%) is at very high criteria, working effectively in groups (99.40%) is at very high criteria, communicating in group activities (75%) is at high criteria, and having responsibility for completing group assignments (93.25%) is at very high criteria. Therefore, collaboration skills can not only be honed through teaching and learning activities in class, but also can be honed through practicum learning activities in the laboratory.